Reverse transcription-polymerase chain reaction (RT-PCR) assay for detection and characterization of Alfalfa mosaic virus (AMV) in legume crops applied by ICARDA’s Seed Health and Virology Laboratory - Kumari, Safaa; Moukahel, Abdulrahman (International Center for Agricultural Research in the Dry Areas, 2024)
Alfalfa mosaic virus (AMV, genus Alfamovirus, family Bromoviridae) is a significant plant pathogen affecting a wide range of legume crops across various regions of the world including West Asia and North Africa (WANA) countries. AMV is transmitted by aphids in a non-persistent manner and via seeds of several hosts (including faba bean, chickpea, and lentil). Seed transmission makes managing AMV more challenging, as infected seeds can introduce the virus into new areas and lead to infections in the next growing season, even before aphid vectors are active. Accordingly, seed testing and the use of certified seeds are key strategies to mitigate the spread of AMV as a seed-borne virus. Early detection and accurate diagnosis of viral diseases is critical for the application of appropriate control measures. However, the accuracy and reliability of molecular methods is a fact beyond dispute. This report describes a validated molecular tool for AMV detection and characterization applied by ICARDA’s Seed Health and Virology Laboratory.